2017
DOI: 10.1093/neuros/nyx319
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgical Randomized Controlled Trials—Distance Travelled

Abstract: Several aspects of the design and reporting of RCTs on neurosurgical procedures have improved over time. Better powered and accurately reported trials are needed in neurosurgery to deliver evidence-based care and achieve optimal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…In an effort to remain consistent with the previous work of Vranos et al 7 and Azad et al 8 to characterize and assess the state of neurosurgical RCTs, we utilized the database of RCTs described by Azad et al 8 for our data extraction. The search strategy and review protocol are outlined in the supplementary data of their report.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to remain consistent with the previous work of Vranos et al 7 and Azad et al 8 to characterize and assess the state of neurosurgical RCTs, we utilized the database of RCTs described by Azad et al 8 for our data extraction. The search strategy and review protocol are outlined in the supplementary data of their report.…”
Section: Methodsmentioning
confidence: 99%
“…The search strategy and review protocol are outlined in the supplementary data of their report. In brief, Azad et al 8 searched MEDLINE, Scopus, and the Cochrane Library Controlled Trials Registry from January 2003 to July 2016 aiming to identify randomized trials of neurosurgical procedures used in “cranial and spinal neurosurgical practice, excluding trials of peripheral nerve procedures.” 8 All randomized trials compared one neurosurgical procedure with another neurosurgical procedure, nonsurgical treatment, or no treatment. Studies with <5 patients in each arm and studies that compared drugs, physical therapy, or conventional radiotherapy alone were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…However, the true aim of the framework is to facilitate the conduct of well-designed and well-executed studies in order to facilitate the adoption of innovative techniques, if found to be effective. A recent example is the use of middle meningeal artery (MMA) embolization for chronic subdural hematomas (CSDH), where the majority of conducted studies are case series [ 6 ]. Although this procedure is clearly innovative, many of the studies reported use of MMA embolization for atypical indications (e.g., asymptomatic patients, as “prophylaxis” after surgery) outside the context of ethically approved research.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that routinely collected or observational data can lead to robust conclusions regarding the comparative effectiveness of treatment; however, this is a relatively new field with ongoing methodological challenges. As an example, a recent study found that observational studies based on routinely collected health data could give different answers from subsequent randomized trials on the same clinical questions and may substantially overestimate treatment effects [ 6 ]. Reasons for this are likely multiple, and while this difference could reflect a difference in validity achieved by the different study methodologies, it is important to consider the impact the highly selective populations used for randomized trials could have on research outcomes, in comparison with the broader populations that usually contribute to observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we decline any sort of direct involvement and study-related financial support by the industry, and aim to minimise personal conflict of interests with device manufacturers. This may enable execution and critical appraisal of the study results with less bias 55 56…”
Section: Discussionmentioning
confidence: 99%